Perbandingan Algoritma Elias Omega Dan Algoritma Additive Code Dalam Mengkompresi File Audio Video Interleave (AVI) - Simbolon, Adi Dharma (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2024)
AVI Video Files First introduced in 1992 by Microsoft, AVI videos were all the rage during the 90s and early 2000s. This container can only hold video and audio clips and can also store multiple tracks of each type, but this feature is rarely used. AVI playback is nearly universal, but has some compression limitations that result in larger than average file sizes. One of the problems that often occurs in using video is problems related to the size of the video. If the video size is large, a large storage capacity is required from the recipient. Based on these problems, a data reduction technique is needed or what is usually called a compression technique. The compression technique requires an algorithm in this research. The algorithm used is the Elias Omega algorithm and Addtive Code. The right solution to this problem is compression because the purpose of data compression is to representing digital data with as few bits as possible, the problem above will be solved using the Elias Omega Algoritama and Additive Code in compressing AVI video files. This research produces a performance level of the compression algorithm, it will measure the performance of the AVI Audio Video file compression results according to the parameters which has been specified. From the calculations that have been calculated, it can be concluded that the percentage of compression results for Audio VideoAVI files using the Elias Omega algorithm is 6,600 and the Additive Code algorithm is 6,426.